The role of transformational leadership in achieving administrative creativity: Search exploratory sample of the views of officials in the office Iraqi Ministry of Education (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Testing the current research and effect correlation between Transformational leadership variable manufacturing and variable administrative creativity, as it represented the research problem the extent of the role of transformational leadership in achieving administrative creativity in the office of the Iraqi Ministry of Education, it has been used questionnaire as a tool for data collection, as is the distribution (32) for the sample of the research, which was selected intentional and as director general and assistant general manager and director and deputy director and head of the Division, and represented the premise of the major search existence of liaison and the impact of significantly between transformational leadership and achieve administrative creativity relationship, and the data using spss program analysis were used a number of statistical methods to validate hypothesis, including the correlation coefficient (person) and analysis of simple regression, and the results were identical to the hypothesis of the research, it has been shown, Joe d link and the impact of legal persons between transformational leadership and achieve administrative innovation and against which has been drafting a set of recommendations that will hopefully be taken advantage of them involved in the current research relationship.